Free Fatty Acid Receptors as Mediators and Therapeutic Targets in Liver Disease - Secor, Jordan D.; Fligor, Scott C.; Tsikis, Savas T.; Yu, Lumeng J.; Puder, Mark (Frontiers in Physiology, 2021)
Free fatty acid receptors (FFARs) are a class of G protein-coupled receptors (GPRs) that have wide-ranging effects on human physiology. The four well-characterized FFARs are FFAR1/GPR40, FFAR2/GPR43, FFAR3/GPR41, and FFAR4/GPR120. Short-chain (<6 carbon) fatty acids target FFAR2/GPR43 and FFAR3/GPR41. Medium- and long-chain fatty acids (6-12 and 12-20 carbon, respectively) target both FFAR1/GPR40 and FFAR4/GPR120. Signaling through FFARs has been implicated in non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH), intestinal failure-associated liver disease (IFALD), and a variety of other liver disorders. FFARs are now regarded as targets for therapeutic intervention for liver disease, diabetes, obesity, hyperlipidemia, and metabolic syndrome. In this review, we provide an in-depth, focused summary of the role FFARs play in liver health and disease.